Transient receptor potential channel 1 maintains adherens junction plasticity by suppressing sphingosine kinase 1 expression to induce endothelial hyperpermeability. Issue 1 (27th August 2015) - Tauseef, Mohammad; Farazuddin, Mohammad; Sukriti, Sukriti; Rajput, Charu; Meyer, James Otto; Ramasamy, Suresh Kumar; Mehta, Dolly
ABSTRACT: Stability of endothelial cell (EC) adherens junctions (AJs) is central for prevention of tissue edema, the hallmark of chronic inflammatory diseases including acute respiratory distress syndrome. Here, we demonstrate a previously unsuspected role of sphingosine kinase 1 (SPHK1) in the mechanism by which transient receptor potential channel 1 ( Trpc1 )‐mediated Ca 2+ entry destabilizes AJs. Trpc1 ‐/‐ monolayers showed a 2.2‐fold increase in vascular endothelial (VE)‐cadherin cell‐surface expression above wild‐type (WT) monolayers. Thrombin increased endothelial permeability (evident by a 5‐fold increase in interendothelial gap area and 60% decrease in transendothelial electrical resistance) in WT but not Trpc1 ‐/‐ ECs. Trpc1 ‐/‐ mice resisted the hyperpermeability effects of the edemagenic agonists used and exhibited 60% less endotoxin‐induced mortality. Because sphingosine‐1‐phosphate (S1P) strengthens AJs, we determined if TRPC1 functioned by inhibiting SPHK1 activity, which generates S1P. Intriguingly, Trpc1 ‐/‐ ECs or ECs transducing a TRPC1‐inactive mutant showed a 1.5‐fold increase in basal SPHK1 expression compared with WT ECs, resulting in a 2‐fold higher S1P level. SPHK1 inhibitor SK1‐I decreased basal transendothelial electrical resistance more in WT ECs (48 and 72% reduction at 20 and 50 μM, respectively) than in Trpc1 ‐/‐ ECs. However, SK1‐I pretreatment rescued thrombin‐induced EC permeability in Trpc1 ‐/‐ ECs. Thus, TRPC1 suppression of basal SPHK1 activity enables EC‐barrier destabilization by edemagenic agonists.—Tauseef, M., Farazuddin, M., Sukriti, S., Rajput, C., Meyer, J. O., Ramasamy, S. K., Mehta, D. Transient receptor potential channel 1 maintains adherens junction plasticity by suppressing sphingosine kinase 1 expression to induce endothelial hyperpermeability. FASEB J. 30, 102‐110 (2016). www.fasebj.org